Electrochemical Characteristics of a Cu(II) Schiff Base Complex and Its Interaction with DNA - GUO, FENG; JIA, ZHEN; BO LI, WEN; MEI LI, YU; LING ZHANG, XIU (Asian Journal of Chemistry, 2010)
The Cu(II) Schiff base was synthesized and characterized by elemental analysis, molar conductivity, IR and UV-Visible spectra. The electrochemical characteristics of a mononuclear Cu(II) complex have been studied and the interaction of copper complex with DNA was also studied by cyclic voltammetry and fluorescence spectrum.